Meeting Report on “The International Congress on Autoimmune Pre-disease (2024)” - Justus Ohmes; Afsaneh Mehrpouyan; Julia Wimmer-Groß; Abdul Razzaque Ahmed; Kyle T. Amber; Swayanka Biswas; Angela Christiano; Shirin Emtenani; Stephanie Goletz; Jennifer Elisabeth Hundt; Laura Kirchhoff; Khalaf Kridin; et al. (JID Innovations)
The International Congress on Autoimmune Pre-Disease was organized by the German Research Foundation–founded Research Training Group “Autoimmune Pre-Disease” and took place at the University of Lübeck, Germany, on September 16–17, 2024. The event featured various talks and posters from young researchers and international experts and emphasized early interventions and prevention in autoimmune diseases with a focus on systemic rheumatic diseases, pemphigus, and pemphigoid diseases.